2022
DOI: 10.1088/2051-672x/ac577f
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Corrosion behaviour and hardness of Ni-B4C Composite coated AZ31 Mg alloy using RSM

Abstract: The optimisation of process parameters in the electroplating process is imperative to improve the effectiveness of coating that meets the industry’s requirements. The present study analyses the influence of the electroplating parameters such as bath temperature, current intensity, and plating time on the hardness and corrosion properties of AZ31 Mg alloy. A preliminary electroplating coating was initially done on the AZ31 Mg alloy with zinc and copper. Subsequently, the AZ31 Mg alloy is coated with Ni-B4C comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Hence, it can be concluded that the results of single-factor experiments obtained in the study of multi-factor systems are often of little use for practical application. For the investigation of multi-factor systems, it is most appropriate to use statistical methods of experiment design, which make it possible to obtain models of multi-factor processes with a minimum number of runs [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it can be concluded that the results of single-factor experiments obtained in the study of multi-factor systems are often of little use for practical application. For the investigation of multi-factor systems, it is most appropriate to use statistical methods of experiment design, which make it possible to obtain models of multi-factor processes with a minimum number of runs [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%